Propofol inhibits neuroinflammation and metabolic reprogramming in microglia in vitro and in vivo - Guan, Shuyuan; Sun, Lingbin; Wang, Xihua; Huang, Xirui; Luo, Tao (Frontiers in Pharmacology, 2023)
Microglial activation-induced neuroinflammation is closely related to the development of sepsis-associated encephalopathy. Accumulating evidence suggests that changes in the metabolic profile of microglia is crucial for their response to inflammation. Propofol is widely used for sedation in mechanically ventilated patients with sepsis. Here, we investigate the effect of propofol on lipopolysaccharide-induced neuroinflammation, neuronal injuries, microglia metabolic reprogramming as well as the underlying molecular mechanisms. The neuroprotective effects of propofol (80 mg/kg) in vivo were measured in the lipopolysaccharide (2 mg/kg)-induced sepsis in mice through behavioral tests, Western blot analysis and immunofluorescent staining. The anti-inflammatory effects of propofol (50 μM) in microglial cell cultures under lipopolysaccharide (10 ng/ml) challenge were examined with Seahorse XF Glycolysis Stress test, ROS assay, Western blot, and immunofluorescent staining. We showed that propofol treatment reduced microglia activation and neuroinflammation, inhibited neuronal apoptosis and improved lipopolysaccharide-induced cognitive dysfunction. Propofol also attenuated lipopolysaccharide-stimulated increases of inducible nitric oxide synthase, nitric oxide, tumor necrosis factor-α, interlukin-1β and COX-2 in cultured BV-2 cells. Propofol-treated microglia showed a remarkable suppression of lipopolysaccharide-induced HIF-1α, PFKFB3, HK2 expression and along with downregulation of the ROS/PI3K/Akt/mTOR signaling pathway. Moreover, propofol attenuated the enhancement of mitochondrial respiration and glycolysis induced by lipopolysaccharide. Together, our data suggest that propofol attenuated inflammatory response by inhibiting metabolic reprogramming, at least in part, through downregulation of the ROS/PI3K/Akt/mTOR/HIF-1α signaling pathway.